2016
DOI: 10.1016/j.virol.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Circovirus in domestic and wild carnivores: An important opportunistic agent?

Abstract: Circoviruses are relatively novel pathogens with increased importance in canids. In this study, we first screened the presence of dog circovirus (DogCV) by molecular methods from a total number of 389 internal organ samples originating from 277 individuals of domestic dogs and wild animals including wolves, foxes and badgers. All the animals originated from Central-Southern Italy, specifically from Abruzzi and Molise regions, areas hosting several natural parks. DogCV was detected in 9/34 wolves (P=26.4%; IC 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
74
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 13 publications
11
74
2
Order By: Relevance
“…Overall, 81.69% of the CanineCV-positive samples tested positive for another pathogen. Compared with the controls, co-infections were remarkably related with disease (p < 0.00001), which was in agreement with the results reported in previous studies (Gizzi et al, 2014;Li et al, 2013;Zaccaria et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, 81.69% of the CanineCV-positive samples tested positive for another pathogen. Compared with the controls, co-infections were remarkably related with disease (p < 0.00001), which was in agreement with the results reported in previous studies (Gizzi et al, 2014;Li et al, 2013;Zaccaria et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…CanineCV was strongly associated to the occurrence of enteric disease only in co-infections with other, well-recognised pathogens (CPV or CCoV). While previous reports accounted for a primary role of CanineCV in the development of clinical disease (Li et al, 2013;Decaro et al, 2014), subsequent studies suggested that this virus can act as entheropathogen mainly when associated to other pathogens (Hsu et al, 2016;Thaiwong et al, 2016;Zaccaria et al, 2016). Our study has shown a high frequency of detection of CanineCV in diarrheal dogs (32.42%), similar to that reported in a recent study from China (28%) (Hsu et al, 2016) but greater with respect to a previous survey conducted in USA (11.3%) (Li et al, 2013) and to two very recent studies conducted in Germany (20.1%, Gentil et al, 2017;3.64%, Anderson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DuCV infection may cause immunosuppression in ducks and the predisposed ducks are prone to be coinfected by other bacterial and viral pathogens (Soike et al., ; Zhang et al., ). The coinfection cases of parvovirus and circovirus were detected in pigs (Sun et al., ), canines (Anderson et al., ; Thaiwong, Wise, Maes, Mullaney, & Kiupel, ) and wild carnivores (Zaccaria et al., ). However, little is known about parvovirus coinfection with circovirus in ducks.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine circovirus 1 (PCV1) was first described at the Robert Koch Institute, Berlin [19]. Other members of this family are PCV2, several avian circoviruses [18], and recently new circoviruses have been isolated from mammals: bat [20,21], dogs [22,23,24,25], mink [26,27], and others. Circoviruses are non-enveloped spherical (16–18 nm) particles (Figure 1) with a single-stranded and circular small DNA genome.…”
Section: Introductionmentioning
confidence: 99%